Proteome characterization of small extracellular vesicles from spared nerve injury model of neuropathic pain - Jean-Toussaint, Renee (J Proteomics, 2019)
Exosomes are 30-150 nm extracellular vesicles mediating intercellular communication. Disease states can alter exosome composition affecting the message carried and thereby, its functional impact. The objective of this study was to identify proteins present in these vesicles in a mouse model of neuropathic pain induced by spared nerve injury (SNI). Small extracellular vesicles (sEVs) were purified from serum four weeks after SNI surgery and the protein composition was determined using tandem mass spectrometry and cytokine array. Proteomic analysis detected 274 gene products within sEVs. Of these, 24 were unique to SNI model, 100 to sham surgery control and five to naïve control samples. In addition to commonly expressed sEVs proteins, multiple members of serpin and complement family were detected in sEVs. Cytokine profiling using a membrane-based antibody array showed significant upregulation of complement component 5a (C5a) and Intercellular Adhesion Molecule 1 (ICAM-1) in sEVs from SNI model compared to sham control. We observed a differential distribution of C5a and ICAM-1 within sEVs and serum between sham and SNI, indicating changes from local or paracrine to long distance signaling under neuropathic pain. Our studies suggest critical roles for cargo sorting of vesicular proteins in mediating signaling mechanisms underlying neuropathic pain.